Analysis of Subsurface Hardness during the Wet and Dry Seasons in the Rice Fields of Semarang Village, Bengkulu City, Using the MASW Seismic Method - Muhammad Arief Dermawansyah Nusan; Lubis, Ashar Muda; Elfi Yuliza (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
The mechanical properties of soil in agricultural land are greatly influenced by seasonal changes, which can affect productivity and food security. This study aims to analyze the effects of wet and dry seasons on the mechanical properties of subsoil in the rice fields of Semarang Village, Bengkulu City, and their implications for land management that supports food security. The method used was Multichannel Analysis of Surface Waves (MASW) with data acquisition at 24 points using 24 geophones (2 m spacing, 5 m offset). The data was then processed using WinMASW Professional 5.0 software to obtain a 2D model of shear wave velocity (Vs) and Poisson's Ratio to a depth of 30 m. The results showed that during the wet season, the soil was dominated by low Vs values (< 350 m/s) and high Poisson's Ratios (0.4 0.45), indicating saturated and soft conditions. Conversely, during the dry season, Vs values increased (600–1200 m/s) with lower Poisson Ratios (0.35–0.4), indicating a denser and stiffer subsurface medium. These findings confirm that seasonal variations in water content greatly affect the mechanical properties of the soil. Therefore, MASW-based analysis can be used as a basis for planning adaptive water and agricultural land management to support food security in tropical climates.